Night to Shine and Inspiration Porn: An Examination of Practices in Disability Ministry - Hoggatt, Michael J. (Journal of disability & religion, 2023)
While the Tim Tebow Foundation is celebrated by community members for the outreach to the disability community, others have questioned both the intent and the impact. Specifically, some critics have argued that a Night to Shine is “an embodiment of our highly celebrated, rarely challenged paternalistic relationship between those with disabilities and those without. In the disability community, this type of message… is known as Inspiration Porn”. This investigation examines the concept of “Inspiration Porn” as developed by Stella Young and used by disability rights advocates to determine whether it is an apt descriptor. Upon examination of Night to Shine considering the concept of Inspiration Porn this examination will seek to apply Tumeinski and McNair “What would be better?” framework in order to evaluate both “Night to Shine” and similarly situated events intending to determine what local faith-communities could do better in their efforts to serve, support, and minister to adults labeled with disabilities.